2014
DOI: 10.1080/00028487.2014.892535
|View full text |Cite
|
Sign up to set email alerts
|

Contingents of Southern Flounder from Subtropical Estuaries Revealed by Otolith Chemistry

Abstract: The identification of contingents within populations that exhibit distinct migratory behaviors and patterns of habitat use can lead to the understanding of the fitness consequences of individual variability in a population and an increased understanding of population dynamics. This study examines the variation in migratory behavior and habitat use patterns in Southern Flounder Paralichthys lethostigma in the northwestern Gulf of Mexico, whose populations have declined rapidly over the last 25–30years. The put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…Mixed results have been found in relation to growth variation among resident and migratory fish of other species. Migratory white perch had higher juvenile and adult growth rates than resident fish [16,17], but a study on southern flounder found no advantage of specific residency periods based on several growth proxies [18]. The latter study only focused on first year growth.…”
Section: Discussionmentioning
confidence: 99%
“…Mixed results have been found in relation to growth variation among resident and migratory fish of other species. Migratory white perch had higher juvenile and adult growth rates than resident fish [16,17], but a study on southern flounder found no advantage of specific residency periods based on several growth proxies [18]. The latter study only focused on first year growth.…”
Section: Discussionmentioning
confidence: 99%
“…This trait may result in life history diversity in salinities that fishes inhabit throughout life and during distinct life periods, like the juvenile phase (Able 2005; Kerr et al 2009;Secor and Kerr 2009). In fishes, this diversity has been described by the population contingent hypothesis where different contingents exhibit varying migratory strategies across or residency within salinity thresholds (Clark 1968;Secor 1999;Nims and Walther 2014). In contrast, fish populations may also contain individuals demonstrating continuous gradients of salinity variation without identifiable contingent structure, exhibiting facultative use of variable salinities throughout life (Cucherousset et al 2005;Rohtla and Vetemaa 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Southern Flounder constitute the majority of harvest for the state-managed flounder fishery in the GOM (>10% of flatfish collected in our sampling were identified as Gulf Flounder), yet life history information is currently lacking for Southern Flounder in the Mississippi region. Over the last two decades, research on Southern Flounder life history has focused on the management units in Louisiana (Fischer andThompson 2001, 2004) and Texas (Stunz et al 2000;Glass et al 2008;Nims and Walther 2014). In the most recent regional management profile by the Gulf States Marine Fisheries Commission, data from Louisiana and Texas were used to represent the entire Southern Flounder fishery in the GOM (GSMFC 2015).…”
Section: Discussionmentioning
confidence: 99%